Kinetics of Cholesterol Oxidation in Model Systems and Foods: Current Status - Medina-Meza, Ilce Gabriela; Barnaba, Carlo (Food engineering reviews, 2013)
In the last decades, cholesterol oxidation products (COPs) have been one of the most intense topics in food science because of their biological and pathological effects on human health. The formation of COPs during food processing is a thermodynamically governed phenomenon and, as for all chemical and biochemical reactions, this formation can be controlled through a kinetic monitoring of oxidative trends, in a manner similar to lipid oxidation. The use of kinetics modeling as a powerful predictive tool has increased recently, although its application in lipid oxidation and cholesterol is poor. Despite the abundance of data on the subject, as evidenced by the presence of numerous reviews about the content of COPs in different foods, contributions to the kinetic modeling are isolated. Moreover, the application of this mathematical approach often demonstrates numerous errors in methodology. This paper summarizes the scientific advances in kinetic modeling of thermo- and photo-induced oxidation of cholesterol. We briefly describe the reaction mechanisms of both degradative pathways, with particular attention to involucrate variables. Then, state of the art of mechanistic models that are proposed is discussed in detail. This analysis shows that it is necessary to broaden and deepen the kinetic study of cholesterol oxidative phenomenon from a mechanistic perspective with a more specific application of kinetic principles. The development of effective predictive models may help to monitor COPs during processing of the food and thus prevent their accumulation in the final products.